2016
DOI: 10.1177/0284185116665421
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of handheld ultrasound and automated breast ultrasound in women recalled after mammography screening

Abstract: Background Automated breast volume scanner (ABVS) is an ultrasound (US) device with a wide scanner that sweeps over a large area of the breast and the acquired transverse images are sent to a workstation for reconstruction and review. Whether ABVS is as reliable as handheld US is, however, still not established. Purpose To compare the sensitivity and specificity of ABVS to handheld breast US for detection of breast cancer, in the situation of recall after mammography screening. Material and Methods A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 24 publications
1
12
1
2
Order By: Relevance
“…Additionally, the presence of microcalcifications on mammography was associated with a lower BI-RADS category being assigned by ABUS. Previous studies have reported that neither HHUS nor ABUS could provide additional information regarding ductal carcinoma in situ or invasive ductal carcinoma presenting as microcalcifications [14,16]. In this retrospective review of cases exhibiting microcalcifications on mammography, uncertainty regarding the locational correlation between mammography and US findings and the conservative assessment of microcalcifications before magnification might have affected the BI-RADS grading.…”
Section: Discussionmentioning
confidence: 84%
“…Additionally, the presence of microcalcifications on mammography was associated with a lower BI-RADS category being assigned by ABUS. Previous studies have reported that neither HHUS nor ABUS could provide additional information regarding ductal carcinoma in situ or invasive ductal carcinoma presenting as microcalcifications [14,16]. In this retrospective review of cases exhibiting microcalcifications on mammography, uncertainty regarding the locational correlation between mammography and US findings and the conservative assessment of microcalcifications before magnification might have affected the BI-RADS grading.…”
Section: Discussionmentioning
confidence: 84%
“…We then screened titles and abstracts to exclude 322 articles that did not meet the inclusion criteria or that met the exclusion criteria. We completely evaluated the remaining 82 articles, among which 17 (12 in English, 5 in Chinese) (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) were selected for diagnostic accuracy analysis and 13 (11 in English, 2 in Chinese) (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) were selected for detection rate analysis (Figure 1). Because 8 articles were used for both diagnostic accuracy and detection rate, a total of 22 articles (13-34) were included in this study (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The detected carcinomas had a mean size of 2.1 cm (mean size ranged between 1.6 cm to 2.6 cm) in seven of the 21 studies [ 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. The mean level of malignancy detected was 94% (81–100%) contrasted with non-cancer in all examinations.…”
Section: Resultsmentioning
confidence: 99%
“…The large variation of these positive predictive values is chiefly due to the application of different assessment categories and different sonographic criteria for malignancy. Only three studies reported that all findings were classified as benign post biopsy [ 35 , 39 , 40 ]. Nonetheless, three studies did not specify the follow-up for patients with positive outcomes [ 26 , 33 , 41 ] ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%